Safety of Ramadan fasting in young patients with type 1 diabetes : A systematic review and meta-analysis - Loh, Huai Heng; Lim, Lee Ling; Loh, Huai Seng; Yee, Anne (Asian Association for the Study of Diabetes and Blackwell Pub. Asia, 2019)
Aims/Introduction: Although patients with type 1 diabetes are medically exempt, many insist on fasting during Ramadan. Multiple daily insulin injections (MDI), premixed insulin and continuous subcutaneous insulin infusion (CSII) are commonly used. To date, little is known about the safety of Ramadan fasting in these patients. Materials and Methods: We pooled data from 17 observational studies involving 1,699 patients treated with either CSII or non-CSII (including premixed and MDI) regimen. The study outcomes were the frequencies of hypoglycemia, hyperglycemia and/or ketosis. Given the lack of patient-level data, separate analyses for premixed and MDI regimen were not carried out. Results: The CSII-treated group (n = 203) was older (22.9 – 6.9 vs 17.8 – 4.0 years), and had longer diabetes duration (116.7 – 66.5 vs 74.8 – 59.2 months) and lower glycated hemoglobin (7.8 – 1.1% vs 9.1 – 2.0%) at baseline than the non-CSII-treated group (n = 1,496). The non-CSII-treated group had less non-severe hypoglycemia than the CSIItreated group (22%, 95% CI 13–34 vs 35%, 95% CI 17–55). Of the non-CSII-treated group, 7.1% (95% CI 5.8–8.5) developed severe hypoglycemia, but none from the CSII-treated group did. The non-CSII-treated group was more likely to develop hyperglycemia (12%, 95% CI 3–25 vs 8.8%, 95% CI 0–31) and ketosis (2.5%, 95% CI 1.0–4.6 vs 1.6%, 95% CI 0.1–4.7), and discontinue fasting (55%, 95% CI 34–76 vs 31%, 95% CI 9–60) than the CSII-treated group. Conclusions: The CSII regimen had lower rates of severe hypoglycemia and hyperglycemia/ketosis, but a higher rate of non-severe hyperglycemia than premixed/MDI regimens. These suggest that appropriate patient selection with regular, supervised finetuning of the basal insulin rate with intensive glucose monitoring might mitigate the residual hypoglycemia risk during Ramadan.